If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15=1.6(x+12)
We move all terms to the left:
15-(1.6(x+12))=0
We calculate terms in parentheses: -(1.6(x+12)), so:We get rid of parentheses
1.6(x+12)
We multiply parentheses
1.6x+19.2
Back to the equation:
-(1.6x+19.2)
-1.6x-19.2+15=0
We add all the numbers together, and all the variables
-1.6x-4.2=0
We move all terms containing x to the left, all other terms to the right
-1.6x=4.2
x=4.2/-1.6
x=-2+1/1.6
| p/16=7 | | 6(5+5x)=30 | | 2x-1/3=x+5/5 | | r/31=9 | | x+4x=-5+7x | | 12x+15=-33 | | h/9=-3 | | 4x+16x-5=4(5x+4) | | 2z-4/5=3z+3/10 | | 4(1-2x)=9 | | r+40=80 | | p+10/8=2p-7/4 | | 4(2x−1)−x−4=-1 | | 12.65b-3.75=9.45b-5.35 | | 18x+16-32=180 | | 4(2−x)+15=3(x+3) | | 2.m–8=6 2 | | f-65=14 | | 33.33333333333333333333333333333333x-2=x-6 | | h-7/4=2h+1/3 | | x/5=12. | | 4-2x=x+3 | | 9.68x+21.6-6.23=2.3+17 | | 1/3x-2=x-6 | | 13=k+46 | | 5−2p=3 | | 3x+5-3=4 | | 12y-3(y-3)=6y+8-(y-2) | | 2c-1/3=c+2/4 | | 12=s+70 | | t+11=89 | | j-5/2=j+8/7 |